Functional Safety Compliant Test & Repair Framework for System-on-Chip Lifecycle Management - Harutyunyan, Gurgen E.; Shoukourian, Samvel K.; Tshagharyan, Grigor A.; Zorian, Yervant A. (Mathematical Problems of Computer Science, 2021)
The share of safety-critical systems in electronic and electrical (E/E) devices across multiple domains, especially in automotive industry, is growing at a constant rate. An unhandled failure of any component within the system may compromise the safety of the entire ecosystem. Therefore, regardless of the context of use and level of the hierarchy, all system components must follow the requirements of appropriate safety standard for the development process and in-field operation. In this context, the traditional built-in self-test (BIST) scheme must also meet the safety requirements defined in ISO 26262 in order to be approved for automotive applications. The paper presents a functional safety compliant BIST infrastructure concept that helps to ensure safe test execution throughout the entire System-on-Chip (SoC) lifecycle while maintaining high test quality.